2018
DOI: 10.1097/j.pain.0000000000001466
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of synovial macrophages to rat advanced osteoarthritis pain resistant to cyclooxygenase inhibitors

Abstract: Most advanced knee osteoarthritis (OA) patients experience chronic pain resistant to cyclooxygenase (COX) inhibitors. However, the cells and molecules involved in this advanced OA pain remain poorly understood. In this study, we developed a rat model of advanced knee OA by modification of the monoiodoacetate-induced OA pain model and examined involvement of synovial macrophages in advanced OA pain. Cyclooxygenase inhibitors, such as celecoxib and naproxen, and a steroid were ineffective, but an opioid and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 65 publications
3
43
1
Order By: Relevance
“…Interestingly, an increase in the nerve growth factor, related with persistent pain in OA patients, was also observed [78]. Similar findings were also reported in rat models of monoiodoacetate-induced OA [123]. In contrary to these results, a very recent study by Bailey et al has demonstrated that intra-articular injection of clodronate liposomes in post-traumatic arthritis murine models did not reduce the synovitis, and the M1/M2 ratio was increased in some treated mice, advocating that clodronate liposomes could lead to the depletion not only of the M1 pro-inflammatory macrophages, but also of the M2-like immunomodulator counterparts [124].…”
Section: Liposome-based Anti-inflammatory Approachessupporting
confidence: 81%
“…Interestingly, an increase in the nerve growth factor, related with persistent pain in OA patients, was also observed [78]. Similar findings were also reported in rat models of monoiodoacetate-induced OA [123]. In contrary to these results, a very recent study by Bailey et al has demonstrated that intra-articular injection of clodronate liposomes in post-traumatic arthritis murine models did not reduce the synovitis, and the M1/M2 ratio was increased in some treated mice, advocating that clodronate liposomes could lead to the depletion not only of the M1 pro-inflammatory macrophages, but also of the M2-like immunomodulator counterparts [124].…”
Section: Liposome-based Anti-inflammatory Approachessupporting
confidence: 81%
“…However, its gene expression in OA was downregulated compared with that in normal controls in our study. Many advanced OA patients experience chronic pain resistant to cyclooxygenase (COX) inhibitors (Sakurai et al, 2019). Another study also showed a lack of the chondroprotective effect of cyclooxygenase 2 inhibition in a surgically-induced model of osteoarthritis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are implicated in the regulation of pain sensitivity in multiple conditions (Gong et al, 2016; Shepherd et al, 2018; Sakurai et al, 2019). Macrophage infiltration has been demonstrated in pain-associated synovial tissue from patients with advanced osteoarthritis and in pain-associated models of joint, muscle and paw inflammation (Gong et al, 2016; Shepherd et al, 2018; Sakurai et al, 2019). More importantly, macrophage depletion via clodronate liposomes reduces the elevated pro-inflammatory cytokines and NGF and reduces pain behaviors in a model of arthritis (Sakurai et al, 2019).…”
Section: Macrophages and Regulation Of Nociceptive Signalingmentioning
confidence: 99%
“…Macrophage infiltration has been demonstrated in pain-associated synovial tissue from patients with advanced osteoarthritis and in pain-associated models of joint, muscle and paw inflammation (Gong et al, 2016; Shepherd et al, 2018; Sakurai et al, 2019). More importantly, macrophage depletion via clodronate liposomes reduces the elevated pro-inflammatory cytokines and NGF and reduces pain behaviors in a model of arthritis (Sakurai et al, 2019). Similarly, macrophage depletion prevents local hyperalgesia in response to plantar injection of angiotensin II (Shepherd et al, 2018), and widespread hyperalgesia in response to repeated intra-muscular injection of acidic saline and pro-inflammatory agents (Gong et al, 2016).…”
Section: Macrophages and Regulation Of Nociceptive Signalingmentioning
confidence: 99%
See 1 more Smart Citation